2012
DOI: 10.1038/npp.2012.210
|View full text |Cite
|
Sign up to set email alerts
|

The Volitional Nature of Nicotine Exposure Alters Anandamide and Oleoylethanolamide Levels in the Ventral Tegmental Area

Abstract: Cannabinoid-1 receptors (CB 1 ) have an important role in nicotine reward and their function is disrupted by chronic nicotine exposure, suggesting nicotine-induced alterations in endocannabinoid (eCB) signaling. However, the effects of nicotine on brain eCB levels have not been rigorously evaluated. Volitional intake of nicotine produces physiological and behavioral effects distinct from forced drug administration, although the mechanisms underlying these effects are not known. This study compared the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…This is in line with previous findings from the ventral tegmental area showing enhanced levels of the eCBs arachidonoylethanolamide and 2-arachidonoyl-glycerol after nicotine self-administration (Buczynski et al 2013). It is also in agreement with previous studies showing that antagonists targeting nAChRs on dopaminergic terminals impair eCB-signaling (Partridge et al 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous findings from the ventral tegmental area showing enhanced levels of the eCBs arachidonoylethanolamide and 2-arachidonoyl-glycerol after nicotine self-administration (Buczynski et al 2013). It is also in agreement with previous studies showing that antagonists targeting nAChRs on dopaminergic terminals impair eCB-signaling (Partridge et al 2002).…”
Section: Discussionsupporting
confidence: 93%
“…On the opposite, activation of CB1Rs or inhibition of eCB metabolism enhances nicotine self-administration and expression of nicotine-induced place preference (Merritt et al 2008;Gamaleddin et al 2013). Interestingly, eCB levels are altered by acute and repeated nicotine exposure (Gonzalez et al 2002;Buczynski, Polis, & Parsons 2013), and the endogenous ligand for the nicotinic acetylcholine receptor (nAChR), acetylcholine, appears to regulate eCB-mediated plasticity in the striatum (eCB-LTD) (Partridge et al 2002;Adermark 2011). The striatal eCB system has repeatedly been linked to neuronal adaptations that form persistent drug-related habits and addictive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that nicotine-induced VTA 2-AG formation is sensitized following CNE in a manner independent of the volitional nature of drug exposure [e.g., similar sensitization induced by either nicotine self-administration (SA) or response-independent administration] ( Fig. 1A) (14). To determine the signaling mechanisms influenced by this aberrant 2-AG response, we screened the remaining microdialysate aliquots from these same subjects for temporal changes in neurotransmitter content.…”
Section: Resultsmentioning
confidence: 99%
“…Potent and selective diacylglycerol lipase inhibitors are characterized and used in ex vivo electrophysiology and in vivo behavioral analyses to demonstrate that this mechanism plays a prominent role in the dysregulation of ventral tegmental dopamine neurons following nicotine exposure. (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation